Differential gene expression in the oxyntic and pyloric mucosa of the young pig. - Michela Colombo; Davide Priori; Paolo Trevisi; Paolo Bosi (PLoS ONE, 2014)
The stomach is often considered a single compartment, although morphological differences among specific areas are well known. Oxyntic mucosa (OXY) and pyloric mucosa (PYL, in other species called antral mucosa) are primarily equipped for acid secretion and gastrin production, respectively, while it is not yet clear how the remainder of genes expressed differs in these areas. Here, the differential gene expression between OXY and PYL mucosa was assessed in seven starter pigs. Total RNA expression was analyzed by whole genome Affymetrix Porcine Gene 1.1_ST array strips. Exploratory functional analysis of gene expression values was done by Gene Set Enrichment Analysis, comparing OXY and PYL. Normalized enrichment scores (NESs) were calculated for each gene (statistical significance defined when False Discovery Rate % <25 and P-values of NES<0.05). Expression values were selected for a set of 44 genes and the effect of point of gastric sample was tested by analysis of variance with the procedure for repeated measures. In OXY, HYDROGEN ION TRANSMEMBRANE TRANSPORTER ACTIVITY gene set was the most enriched set compared to PYL, including the two genes for H+/K+-ATPase. Pathways related to mitochondrial activity and feeding behavior were also enriched (primarily cholecystokinin receptors and ghrelin). Aquaporin 4 was the top-ranking gene. In PYL, two gene sets were enriched compared with OXY: LYMPHOCYTE ACTIVATION and LIPID RAFT, a gene set involved in cholesterol-rich microdomains of the plasma membrane. The single most differentially expressed genes were gastrin and secretoglobin 1A, member 1, presumably located in the epithelial line, to inactivate inflammatory mediators. Several genes related to mucosal integrity, immune response, detoxification and epithelium renewal were also enriched in PYL (P<0.05). The data indicate that there is significant differential gene expression between OXY of the young pig and PYL and further functional studies are needed to confirm their physiological importance.